2016
DOI: 10.3800/pbr.11.96
|View full text |Cite
|
Sign up to set email alerts
|

Larvae of the threadsail filefish <i>Stephanolepis cirrhifer</i> feed on eggs and planulae of the jellyfish <i>Aurelia</i> sp. under laboratory conditions

Abstract: Although population dynamics of the egg and planula stages of jellyfish are key factors that predict the abundance of polyps and subsequent jellyfish blooms, information about predation on these stages of jellyfish is lacking. We examined whether threadsail filefish Stephanolepis cirrhifer, an efficient predator of Aurelia sp. medusae in the wild, could feed on eggs or planulae of Aurelia under laboratory conditions. S. cirrhifer larvae at 17 days post hatching (dph) with 4.9±0.8 mm standard length fed on sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this regard, S. cirrhifer is also a very promising biocontrol agent. Aquaculture and hatchery production of S. cirrhifer is becoming increasingly popular in Japan and few other countries (An et al., 2011; Khosravi & Lee, 2017; Miyajwia‐Taga et al., 2016). Combining their high market value and high performance in skin fluke egg consumption, this species could be a good target for multispecies aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, S. cirrhifer is also a very promising biocontrol agent. Aquaculture and hatchery production of S. cirrhifer is becoming increasingly popular in Japan and few other countries (An et al., 2011; Khosravi & Lee, 2017; Miyajwia‐Taga et al., 2016). Combining their high market value and high performance in skin fluke egg consumption, this species could be a good target for multispecies aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…However, interest has grown on the continuously increasing reports of fish preying on medusae. This is due to the possibility of medusivorous fish playing a significant role in controlling jellyfish blooms by feeding on jellyfish adults or even on their eggs and planulae (see Arai 2005 for a review and Miyajima-Taga et al 2016 for recently reported examples). These blooms have become a major concern for the regulation of fish stocks mainly because jellyfish, as voracious zooplankton feeders (Purcell 2003), may prey on fish larvae and compete with zooplanktivorous fish for food (Möller 1984, Purcell & Arai 2001, Brodeur et al 2008).…”
mentioning
confidence: 99%